Intercultural Public Relations Realities and Reflections in Practical Contexts - Ni, Lan; Schlupp, Qi Wang; Sha, Bey-Ling
This book continues the groundbreaking work begun in Intercultural Public Relations: Theories for Managing Relationships and Conflicts with Strategic Publics (Routledge, 2018), by applying the theoretical framework of intercultural public relations to actual practice.